A Digest of the Laws of the State of Connecticut. (vol. 1, 1822) Chapter X, Trespass on the Case, p. 552 - (:unkn) unknown (General Publisher, 1822)
Required guns to be made innoxious before transfering to an "incautious person."
--
Keywords: TRANSFER